Therapeutic work with sexually abused children - Wickham, Randall Easton (SAGE, 2002)
Therapeutic Work with Sexually Abused Children is a creative and practical guide for professionals working directly with those who have suffered sexual abuse and their carers. The trauma of sexual abuse experienced in childhood can inevitably be severe and enduring.